Identification of a Novel Insertion Site HVT-005/006 for the Generation of Recombinant Turkey Herpesvirus Vector - Zai, Xusheng; Shi, Bin; Shao, Hongxia; Qian, Kun; Ye, Jianqiang; Yao, Yongxiu; Nair, Venugopal; Qin, Aijian (Frontiers in Microbiology, 2022)
Turkey herpesvirus (HVT) is widely used as a successful live virus vaccine against Marek’s disease (MD) in chickens for more than 5 decades. Increasingly HVT is also used as a highly effective recombinant vaccine vector against multiple avian pathogens. Conventional recombination, recombineering techniques on cloned viral genomes, and more recently, gene editing methods are used for the generation of recombinant HVT-based vaccines. In this study, we used NHEJ-dependent CRISPR/Cas9-based approaches to insert the mCherry cassette for screening the HVT genome for identifying new potential sites for the insertion of foreign genes. A novel intergenic site HVT005/006 in the unique long (UL) region of the HVT genome was identified from where the mCherry was expressed stably. To confirm whether this site was suitable for the insertion of other exogenous genes, haemagglutinin (HA) of H9N2 virus was inserted into this site and a recombinant HVT-005/006-HA was rescued. The recombinant HVT-HA can grow well and express HA protein stably which demonstrated that HVT005/006 is a promising site for the foreign gene insertion.